Probing the origins, II. unravelling lithium depletion and stellar motion: intrinsic stellar properties drive depletion, not kinematics - Dantas, Maria Luiza L.; Smiljanic, R.; Romano, D.; Guiglion, Guillaume; Magrini, L.; Tissera, P. B.; Souza, Rafael S. de (Astronomy and astrophysics, 2025)
Methods. We analysed the chemo-dynamics of a set of 1188 thin-disc dwarf stars observed by the Gaia-ESO survey, previously classified into six metallicity-stratified groups via hierarchical clustering (HC), ranging from metal-poor to super-metal-rich. We examined several features, such as effective temperatures, masses, and dynamic properties. We also implemented a parametric survival analysis using penalised splines (logistic distribution) to quantify how stellar properties and motion (or migration) direction jointly influence Li depletion patterns. - Results. Stars in our sample that seemingly churned outwards are predominantly Li-depleted, regardless of their metallicities. These stars are also the oldest, coldest, and least massive compared to those in the same HC group that either churned inwards or kept their orbital radii. Our survival analysis confirms temperature as the primary driver of Li depletion, followed by metallicity and age, while migration direction shows negligible influence. Additionally, the proportion of outward-churned stars increases with increasing metallicity, making up more than 90% of our sample in the most metal-rich group. - Conclusions. The increasing proportion of outward-churned stars with higher metallicity (and older ages) indicates their dominant influence on the overall trend observed in the [Fe/H]-A(Li) space for stellar groups with [Fe/H]>0. The survival model reinforces the finding that the observed Li depletion stems primarily from intrinsic stellar properties (cool temperatures, higher metallicity, and old ages) rather than migration history. This suggests the metallicity-dependent depletion pattern emerges through stellar evolution rather than Galactic dynamical processes.
Gesehen am 20.01.2026